DEVELOPMENT OF A NUMERICAL ALGORITHM BASED ON THE FINITE ELEMENT METHOD FOR STUDYING FLOWS IN CHANNELS ("Conference on Universal Science Research 2023", 2024)
The study of fluid flows in channels is crucial for various engineering applications, such as in the design of hydraulic systems, air conditioning, and environmental fluid dynamics. The finite element method (FEM) is a powerful numerical technique used to solve complex fluid flow problems. This article presents the development of a numerical algorithm based on the finite element method for studying flows in channels. The algorithm is designed to accurately simulate and analyze fluid flows in channels of arbitrary geometries and boundary conditions. The implementation details and validation of the algorithm are discussed, demonstrating its effectiveness in solving practical fluid flow problems. The article concludes with a discussion on the potential applications and future developments of the algorithm in the field of fluid dynamics.